Implementasi Kebijakan Rekrutmen PPPK Teknis Kota Sawahlunto Tahun 2022 - Tio Pradena Putra; Roni Ekha Putera (Musamus Journal of Public Administration, 2023)
This article discusses the Indonesian government's efforts to address the needs of ASN employees, as well as the number of honorary employees who have served for years but have not been able to be appointed as ASN employees. By understanding the efforts, steps, and policies implemented by the government, it can be assessed the strategy for recruiting employees other than PNS, namely PPPK employees. The writing of this article uses a qualitative approach using descriptive methods. Meanwhile, the data collection technique used was a literature study that utilized books, journal articles, newspapers, online news, and websites of related institutions. The important findings from this paper are first, the government's response to the problem of employee needs with the PPPK Technical acceptance policy. Second, coordination is carried out by the regional government with the central government regarding the formation of technical staff needs. Third, the ability of honorary employees who have not met the competency standards applied by the supervisory agency, so that after the procurement of Technical PPPK employees has not been maximized. It can be seen from the number of selection participants who did not pass the threshold value, as a result the formation was left vacant by the government. These factors complicate the government's efforts to reformulate ASN employees. Keywords: Honorary, Policy, PPPK, Recruitment.